BIOASSAY DEVELOPMENT USING PEA (Pisum sativum L.) - Ramal Yusuf; Paul Kristiansen; Nigel Warwick (AGROLAND: The Agricultural Sciences Journal, 2014)
The term bioassay is used to describe the use of living material to test the effect of known and putative biologically active substances. In places where advanced analytical equipment is not available, rapid screening using simple, affordable methods is needed. Seeds of Seeds of peas were germinated (Arditti and Dunn, 1969) and grown in the dark at 20°C for 2 days. Five pre-germinated seeds immersed in 30 mL solution containing test solutions of auxins (IBA), cytokinins (kinetin) and a gibberellin (GA3) all seeds were distributed at randomly to Petri dishes containing the test solution. Auxin activity peak was equivalent to 0.005 µM, while cytokinin activity peaked at 0.5 µM, and gibberellin at 0.5 to 5 µM based on root measurement.   KeyWords : Bioassay, elongation, Pea.